Preferential procurement in the public sector: the case of Amathole - Smallwood, John; Ncunyana, Nceba; Emuze, Fidelis (University of the Free State, 2011)
The end of the apartheid era in South Africa ushered in a new institutional environment through changes to legislative frameworks in government depart-ments. A key aspect of the transformation is the economic empowerment of the mainly historically disadvantaged groups in the country through procurement. The thrust of the issue is the assessment of the extent of compliance with Act No. 5 of 2000: Preferential Procurement Policy Framework Act (PPPFA), 2000 at government departments, with particular focus on the Amathole region of the Eastern Cape Province. The assessment was undertaken in a qualitative and quantitative research study conducted among key construction industry stakeholders such as public-sector clients, architects, engineers, and quantity surveyors based within the Amathole region. Selected findings include that there is a perceived low level of awareness of preferential procurement in the public sector as the majority of the institutions investigated have not completely implemented procurement responsibilities as a dedicated function within their organisations. Another significant finding arising from the study is that there are conflicting perceptions among consultants regarding procurement strategies for different types of project.

Die einde van die apartheidsera in Suid-Afrika het ‘n nuwe institusionele om- gewing deur veranderinge aan wetgewingsraamwerke in regerings-departemente ingelei. ‘n Sleutelaspek van die transformasie is die ekonomiese bemagtiging van die hoofsaaklik historiese agtergeblewene groepe in die land deur verkryging. Die kruks van die saak is die assessering van die omvang van inwilliging met Wet No. 5 van 2000: Wet op Raamwerk vir Voorkeurverkrygingsbeleid deur regeringsdepartemente met spesifieke fokus op die Amathole streek van die Oos-Kaapprovinsie. Die assessering is deur ‘n kwalitatiewe en kwantitatiewe navorsingstudie onder sleutelkonstruksie industrie-aandeelhouers soos openbare sektor kliënte, argitekte, ingenieurs, en bourekenaars binne die Amathole streek gedoen. Geselekteerde bevindings sluit in dat daar ‘n lae vlak van bewustheid oor voorkeurverkryging in die openbare sektor is omdat die meerderheid instansies wat ondersoek is nie volledig verkrygingsverantwoordelikhede as ‘n toegewyde funksie binne hul organisasies geïmplimenteer het nie. ‘n Ander noemenswaardige bevinding uit die studie is die botsende persepsies onder konsultante aangaande die strategieë vir verskillende projektipes.
Keywords: Construction; Consultants; Procurement; Public sector; South Africa